Health and lifestyle factors associated with sexual difficulties in men - results from a study of Australian men aged 18 to 55 years - Marisa Schlichthorst; Lena A. Sanci; Jane S. Hocking (BMC, 2016)
Abstract Background Sexual difficulties (SD) are common among men of all ages and can have considerable impact on quality of life and indications for future health. SD are associated with mental and physical wellbeing and with relationship satisfaction, yet they are rarely discussed with medical professionals who are often ill equipped to assess and manage them. This paper provides an updated overview on the status of SD in Australian men from 18 to 55 years of age and will form a baseline comparison for future analyses of SD based on Ten to Men data. Methods We used data from Ten to Men, the Australian Longitudinal Study on Male Health. SD was measured using eight items capturing specific sexual difficulties. We examined associations of a range of health and lifestyle factors (smoking, alcohol consumption, illicit drug use, obesity and new sexual partners, self-rated health status, disability, pain medication, diagnosed physical and mental health conditions) with each SD using logistic regression. The sample included 12,636 adult males who had previously been sexually active. Analysis was stratified by age (18-34 years versus 35-55 years). Results This paper shows that experiencing SD is relatively common among Australian men - overall half the sample (54 %; 95 % CI: 0.53-0.55) experienced at least one SD for more than 3 months over the past 12 months. While more common in older men aged 45 to 55 years, almost half the 18 to 24 year old men (48 %) also reported at least one SD highlighting that SD affects men of all ages. We found that SDs were associated with both lifestyle and health factors, although the strongest associations were observed for health factors in both age groups, in particular poor self-rated health, having a disability and at least one mental health condition. Lifestyle factors associated with SDs in men of all ages included smoking, harmful alcohol consumption and drug use in the past 12 months. Obesity was only associated with an increased rate of SD in men aged 35 to 55 years. Conclusion Sexual difficulties are common among men of all ages and increasingly more prevalent as men grow older. They are strongly associated with both health and lifestyle factors. With previous literature showing that SDs can be a precursor of an underlying or developing physical and mental health condition, it is imperative that sexual health and sexual functioning is discussed with a doctor as part of a standard health check and across the lifespan.